Transforming growth factor β1 (TGF-β1) activates hepcidin mRNA expression in hepatocytes - Chen, Simeng; Spasić Vujić, Maja; Altamura, Sandro; Breitkopf-Heinlein, Katja; Dooley, Steven; Muckenthaler, Martina (The journal of biological chemistry, 2016)
The hepatic hormone hepcidin is the master regulator of systemic iron homeostasis. Its expression level is adjusted to alterations in iron levels, inflammatory cues, and iron requirements for erythropoiesis. Bone morphogenetic protein 6 (BMP6) contributes to the iron-dependent control of hepcidin. In addition, TGF-β1 may stimulate hepcidin mRNA expression in murine hepatocytes and human leukocytes. However, receptors and downstream signaling proteins involved in TGF-β1-induced hepcidin expression are still unclear. Here we show that TGF-β1 treatment of mouse and human hepatocytes, as well as ectopic expression of TGF-β1 in mice, increases hepcidin mRNA levels. The hepcidin response to TGF-β1 depends on functional TGF-β1 type I receptor (ALK5) and TGF-β1 type II receptor (TβRII) and is mediated by a noncanonical mechanism that involves Smad1/5/8 phosphorylation. Interestingly, increasing availability of canonical Smad2/3 decreases TGF-β1-induced hepcidin regulation, whereas the BMP6-hepcidin signal was enhanced, indicating a signaling component stoichiometry-dependent cross-talk between the two pathways. Although ALK2/3-dependent hepcidin activation by BMP6 can be modulated by each of the three hemochromatosis-associated proteins: HJV (hemojuvelin), HFE (hemochromatosis protein), and TfR2 (transferrin receptor 2), these proteins do not control the ALK5-mediated hepcidin response to TGF-β1. TGF-β1 mRNA levels are increased in mouse models of iron overload, indicating that TGF-β1 may contribute to hepcidin synthesis under these conditions. In conclusion, these data demonstrate that a complex regulatory network involving TGF-β1 and BMP6 may control the sensing of systemic and/or hepatic iron levels.
Gesehen am 20.08.2019